Originalism and Non-Originalism as Legal Hermeneutics - Manuel Lázaro Pulido (University of Bologna Law Review, 2025)
One of the hermeneutic elements that are decisive in the development of legislative acts and judicial decisions is the interpretation of the Constitution, the pillar of the legal system. In the United States, the debate on the interpretation of the Constitution by the Supreme Court has become a classic of constitutional law and, therefore, affects reflection on legal hermeneutics. This paper examines originalist and non-originalist approaches to constitutional interpretation and explores how political positions shape hermeneutic analysis, even in continental European legal systems, and specifically in the Spanish one.